Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.22146/jpsi.17276
|View full text |Cite
|
Sign up to set email alerts
|

Mahasiswa dan Internet: Dua Sisi Mata Uang? Problematic Internet Use pada Mahasiswa

Abstract: Abstract. Problematic Internet Use (PIU) is one of the negative effects of the internet use, but we can rarely find publications on PIU of Indonesian's college students, especially college students in Jakarta. The purpose of this research was to describe PIU among college students in Jakarta. The Generalized Problematic Internet Use Scale 2 was used to collect data of a total of 474 college students from three universities in Jakarta. The results showed that: a) For preference for online social interaction sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
3
0
3
Order By: Relevance
“…The use of the internet especially social media as substitute face-to-face social interaction that can make young adults experiencing problematic internet use. This corresponds to research by Reinaldo & Sokang [3] which found that young adults with high problematic internet use is an individual use the internet more often than usual to do some social activities such as accessing social media sites. More detailed relationship between the two variables can be explained through hypothesis test between loneliness and the dimensions of problematic internet use.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The use of the internet especially social media as substitute face-to-face social interaction that can make young adults experiencing problematic internet use. This corresponds to research by Reinaldo & Sokang [3] which found that young adults with high problematic internet use is an individual use the internet more often than usual to do some social activities such as accessing social media sites. More detailed relationship between the two variables can be explained through hypothesis test between loneliness and the dimensions of problematic internet use.…”
Section: Discussionsupporting
confidence: 86%
“…PIU often found in young adults. This can be explained by Reinaldo & Sokang [3] stated that students aged 21 to 26 years who are included in the young adult tend to have difficulty managing behavior in using the internet and have the urge to be online all the time. Many factors can cause PIU in young adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ditemukan beberapa penelitian yang menunjukkan bahwa fenomena problematic internet use umumnya terjadi pada mahasiswa (Reinaldo & Sokang, 2016;Liu & Potenza, 2007;Kandell, 1998;Morahan-Martin & Schumacher, 2000). Mahasiswa berada pada masa remaja akhir dan dewasa awal (16-24 tahun), dimana mereka berada pada periode kritis dalam perkembangan sosial dan emosional sehingga rentan terhadap penggunaan internet yang bermasalah (Odaci & Kalkan, 2010).…”
Section: Aunclassified
“…Hal ini dikarenakan siswa yang terkena PIU akan berupaya untuk berinteraksi dengan internet secara online demi mencari kesenangan atau basic need (Caplan, 2003;Ceyhan, 2011). Mereka tidak lagi menggunakan internet sebagai media edukasi melainkan menyimpang untuk tujuan-tujuan lain diluar materi pelajaran (Sokang, 2016) sehingga berpengaruh pada prestasi akademik mereka. Selain itu siswa yang diketahui rendah dalam motivasi berprestasinya akan dapat berpengaruh pada rendah pula kemampuannya dalam menyelesaikan masalah (Masfuah, 2016).…”
Section: Pendahuluanunclassified